RETRACTED: Exosomal miR-128-3p Promotes Epithelial-to-Mesenchymal Transition in Colorectal Cancer Cells by Targeting FOXO4 via TGF-β/SMAD and JAK/STAT3 Signaling - Bai, Jian; Zhang, Xue; Shi, Dongdong; Xiang, Zhenxian; Wang, Shuyi; Yang, Chaogang; Liu, Qing; Huang, Sihao; Fang, Yan; Zhang, Weisong; Song, Jialin; Xiong, Bin (Frontiers in Cell and Developmental Biology, 2021)
Epithelial-to-mesenchymal transition (EMT) is a key process that occurs during tumor metastasis, affecting a variety of malignancies including colorectal cancer (CRC). Exosomes mediate cell-cell communication by transporting cell-derived proteins and nucleic acids, including microRNAs (miRNAs). Exosomal delivery of miRNAs plays an important role in tumor initiation, development, and progression. In this study, we investigated the effect of exosomal transfer between CRC cells and aimed to identify specific miRNAs and downstream targets involved in EMT and metastasis in CRC cells. High expression of miR-128-3p was identified in exosomes derived from EMT-induced HCT-116 cells. Altered miR-128-3p expression in CRC cells led to distinct changes in proliferation, migration, invasion, and EMT. Mechanistically, miR-128-3p overexpression downregulated the expression of FOXO4 and induced the activation of TGF-β/SMAD and JAK/STAT3 signaling in CRC cells and xenografted tumors, which led to EMT. Clinically, high expression of miR-128-3p was significantly associated with perineural invasion, lymphovascular invasion, tumor stage, and CA 19-9 content in CRC patients. We revealed that exosomal miR-128-3p regulates EMT by directly suppressing its downstream target gene FOXO4 to activate TGF-β/SMAD and JAK/STAT3 signaling, and the properties of the miR-128-3p/FOXO4 axis were horizontally transferred via exosomal delivery. In turn, exosomal miR-128-3p could be considered as a new therapeutic vehicle for CRC.